TRICHOSCOPY - A USEFUL TOOL IN THE DIAGNOSIS OF TEMPORAL TRIANGULAR ALOPECIA - Santiago, Felicidade; Guiote, Victoria (Journal of the Portuguese Society of Dermatology and Venereology, 2014)
The authors describe the case of a healthy 3-year-old boy with temporal triangular alopecia, and discuss the main clinical and trichoscopic aspects of this condition, comparing it, from a trichoscopic point of view, with other causes of focal alopecia.